MEMAHAMI KEBIJAKAN PEMBINAAN PEDAGANG KAKI LIMA SURABAYA KAJIAN TERHADAP PERDA KOTA SURABAYA NO. 17 TAHUN 2003 - Tualeka, Basa Alim (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2021)
The research “understands the policy of fostering street vendors (PKL) in Surabaya, a study of the Surabaya City Regulation no. 17 of 2003 resulted in the conclusion that a) PKL assisted by the Surabaya City Government have a unique character, on the one hand they receive assistance from the Surabaya City Government but on the other hand as a party against the Surabaya City Government policies regarding various policies that touch the interests of street vendors, In general, the PKL fostered character has calm in doing business so that they become business partners of the Surabaya City Government, b) PKL assisted by the Surabaya City Government have improved their welfare both financially and socially, 2) The Surabaya City Government has realized various efforts to foster street vendors so as to create a clean, orderly, beautiful and safe city of Surabaya. This research was conducted on street vendors and the Surabaya city government using qualitative research by opening up the possibility of various information materials from all sources. Keywords: policy, coaching, realization of coaching.